Nosocomial bacterial infections in Victoria decreased during the COVID-19 pandemic. Issue 4 (July 2023) - Asgill, Tess F; Stupart, Douglas
Background: A number of infection control interventions were implemented during the COVID-19 pandemic in order to reduce the spread of this virus. Objective: The purpose of this study was to determine if these interventions were associated with reduced nosocomial bacterial infections in Victoria, Australia. Methods: Observational data were obtained from the Victorian Healthcare Associated Infection Surveillance System (VICNISS) based on admitted hospital patients in two 6-month timeframes representing pandemic and pre-pandemic hospital practices. Data were collected for surgical site infections, Staphylococcus aureus bacteraemia, Clostridioides difficile infection, and central line-associated bloodstream infections. Results: There was a significant reduction in the rates of S. aureus bacteraemia (0.74 infections/10, 000 bed days pre-pandemic vs. 0.53/10, 000 bed days in the pandemic period [rate ratio 0.72, 95% CI 0.57–0.90]; p = .003) and in C. difficile infections (2.2 infections/10, 000 bed days pre-pandemic vs. 0.86/10 000 bed days in the pandemic era [rate ratio 0.76, 95% C.I. 0.67–0.86]; p <.001). There was no change in the overall rate of surgical site infections or central line-associated infections however. Discussion: The increased emphasis on infection control and prevention strategies during the pandemic period was associated with reduced transmission of S. aureus and C. difficile infections within hospitals.